Dairy product consumption and type 2 diabetes in an Argentinian population: is there an association? - Baraquet, María Lucía (2024)
Fil: Baraquet, María Lucía. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Escuela de Nutrición; Argentina